Comparison of Internal and External Training for the Development of Employees; A study of IndianIT Industry - Biswa Bhusan,; Sar , Ashok Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Training is very crucial in developing the skillsets of the employees and that results in growth of business and skilled employees attract new projects and they are available also for the same. On an average estimate, every employee spends at least 2 to 15 hours in training depending on the job requirements. Interestingly, these days training has become a basic need in every type of big, small or medium enterprises; and offering skill development training and career enhancement can also improve morale and confidence of the employee, which is perfect for more productivity. There are two types of training which normally happens in an organization. One is in house training and the other is training by external training vendors or institutes. This is conceptual paper to understand different concepts related to the various training programs in IT Companies. The data is collected through the secondary research. The study tries to identify which is the suitable training program to be adopted for the IT organizations in some of the contexts.